Mechanochemical synthesis and characterization of calcium-doped ceria oxide ion conductor - Ong, Poh Shing; Tan, Yen Ping; Yap, Taufiq Yun Hin (IOP Publishing, 2009)
Crystalline fluorite-like structure of Ca-doped CeO2 compounds was prepared via mechanochemical synthesis route. An in-depth study was conducted to optimize the processing parameters whereby three different variables associated with the milling process were studied; milling time, revolution per minute (rpm) and solvent medium. This work was conducted in pursuit of developing optimum milling process parameters for Ca-doped CeO2 oxide ion conductors. For the purpose of comparison, calcium-doped ceria samples were also prepared by conventional solid state method using CeO2 and CaCO3. The single phase compounds were characterized by employing differential thermal analysis/thermogravimetry (DTA/TG), X-ray diffractometry (XRD), infrared spectroscopy (IR), inductively coupled – plasma atomic emission spectroscopy (ICP-AES) and scanning electron microscopy (SEM). The electrical conductivity of sintered samples of calcium doped ceria compounds were investigated in air as a function of temperature using AC impedance spectroscopy.